Becoming a mother as a cultural event: A report of a psychoanalytic intervention with new mothers - Melis, Federica (Quaderni di Psicologia Clinica, 2022)
This work aims at contributing to the development of hypotheses regarding the intervention on motherhood, which can support the creation of psychoanalytically oriented services. In particular, an intervention addressed to new mothers that was carried out in the first semester of the pandemic will be reported. In this work, the experience of motherhood is intended as the product of a shared symbolization within the systems of social coexistence, rather than a given change that one has to adapt to in a conformist way. Through the intervention it was possible to find that considering motherhood as a cultural event opens up the possibility for new mothers to identify desires and resources that can be activated to pursue them within the relationships they are involved in.